Real-world treatment patterns and patient-reported outcomes in episodic and chronic migraine in Japan: analysis of data from the Adelphi migraine disease specific programme - Kaname Ueda; Wenyu Ye; Louise Lombard; Atsushi Kuga; Yongin Kim; Sarah Cotton; James Jackson; Tamas Treuer (The Journal of Headache and Pain, 2019)
Abstract Background In Japan, detailed information on the characteristics, disease burden, and treatment patterns of people living with migraine is limited. The aim of this study was to compare clinical characteristics, disease burden, and treatment patterns in people with episodic migraine (EM) or chronic migraine (CM) using real-world data from clinical practice in Japan. Methods This was an analysis of data collected in 2014 by the Adelphi Migraine Disease Specific Programme, a cross-sectional survey of physicians and their consulting adult patients in Japan, using physician and patient questionnaires. We report patient demographics, prescribed treatment, work productivity, and quality-of-life data for people with CM (≥15 headache days/month) or EM (not fulfilling CM criteria). In descriptive analyses, continuous and categorical measures were assessed using t-tests and Chi-squared tests, respectively. Results Physicians provided data for 977 patients (mean age 44.5 years; 77.2% female; 94.5% with EM, 5.5% with CM). A total of 634/977 (64.9%) invited patients (600 with EM; 34 with CM) also provided data. Acute therapy was currently being prescribed in 93.7% and 100% of patients with EM and CM, respectively (p = 0.069); corresponding percentages for current preventive therapy prescriptions were 40.5% and 68.5% (p < 0.001). According to physicians who provided data, preventive therapy was used at least once by significantly fewer patients with EM than with CM (42.3% vs. 68.5%, respectively; p < 0.001). Among patients who provided physicians with information on issues with their current therapy (acute therapy: n = 668 with EM, n = 38 with CM; preventive therapy: n = 295 with EM, n = 21 with CM), lack of efficacy was the most frequently identified problem (acute therapy: EM 35.3%, CM 39.5% [p = 0.833]; preventive therapy: EM 35.3%, CM 52.4% [p = 0.131]). Moderate-to-severe headache-related disability (Migraine Disability Assessment total score ≥ 11) was reported by significantly fewer patients with EM than with CM (21.0% vs. 60.0%, respectively; p < 0.001) among patients who provided data. Conclusions Preventive treatment patterns in people with EM versus CM differ in Japan, with both types of migraine posing notable disease burdens. Our findings demonstrate that more effective migraine therapies are required to reduce the burden of the disease.